Confidentiality of Doctors Handling Patients in Hazardous Communicable Disease Programs, Jambi City - Sugiati, Ratna; Ropii, Imam; Kuntardjo, Carolina (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines the implementation of doctors' professional confidentiality in the care of patients with hazardous communicable diseases at Community Health Centers in Jambi City. It focuses on the legal and ethical tension between mandatory disease reporting and patient privacy. The research employs a non-doctrinal legal research design with a qualitative approach. Data were collected through in-depth interviews with doctors and infectious disease officers, field observations, and analysis of relevant health laws, regulations, and professional codes of ethics. Participants were selected using purposive sampling. The findings show that confidentiality is generally maintained in accordance with health legislation and medical ethical standards through restricted access to patient information, separation of sensitive data, and controlled use of electronic medical records. However, three major challenges were identified: pressure to disclose patient identities, patient reluctance to cooperate due to stigma and fear of discrimination, and vulnerabilities in digital data management systems. These conditions place doctors in a dilemma between maintaining confidentiality and fulfilling public health reporting obligations. The study concludes that effective protection of medical confidentiality requires ethical commitment, clear operational procedures, and stronger data security measures to protect patient rights while supporting communicable disease control.